Spatial localization of cathepsins: Implications in immune activation and resolution during infections - Anes, Elsa; Pires, David; Mandal, Manoj; Azevedo-Pereira, José Miguel (Frontiers in Immunology, 2022)
Cathepsins were first described, as endolysosomal proteolytic enzymes in reference to the organelles where they degrade the bulk of endogenous and exogenous substrates in a slightly acidic environment. These substrates include pathogens internalised via endocytosis and/or marked for destruction by autophagy. However, the role of cathepsins during infection far exceeds that of direct digestion of the pathogen. Cathepsins have been extensively investigated in the context of tumour associated immune cells and chronic inflammation. Several cathepsin-dependent immune responses develop in the endocytic pathway while others take place in the cytosol, the nucleus, or in the extracellular space. In this review we highlight the spatial localization of cathepsins and their implications in immune activation and resolution pathways during infection.